Uncoordinated climate policies: Implications for cross-border lending - Emanuela Benincasa; Gazi Kabas; Steven Ongena (EconPol Forum, 2023)
There are substantial differences across countries regarding climate policy stringency. Banks react to a stricter climate policy at home by increasing their cross-border lending to countries with laxer climate policies. The evidence is consistent with the adverse effect of transitional climate risks on firms, possibly reducing banks' domestic loan portfolio performance. Global coordination in climate policies is needed to prevent race-to-the-bottom behavior
Keywords: 330